(untitled) (Scientific journal of the Fergana State University, 2025)
This research analyzes the characteristics and requirements related to the planning process of physical culture education and upbringing. Physical culture plays a vital role in the physical and mental development of individuals, making it essential to highlight its place and significance in the educational process. The planning process should take into account the goals, methods, and tools of physical education lessons, as well as the individual characteristics and needs of students. This study examines the fundamental principles of physical education, the content of curricula, and the requirements for teachers. Additionally, it emphasizes the social and cultural context of physical education, as well as the importance of applying modern pedagogical approaches and innovative technologies.